Siglecs Modulate Activities of Immune Cells Through Positive and Negative Regulation of ROS Generation - Karmakar, Joyshree; Mukherjee, Kaustuv; Mandal, Chitra (Frontiers in Immunology, 2021)
Reactive oxygen species (ROS) are a group of oxygen-containing highly-reactive molecules produced from oxidative metabolic processes or in response to intracellular signals like cytokines and external stimuli like pathogen attack. They regulate a range of physiological processes and involved in innate immune responses against infectious agents. Deregulation of ROS contributes to a plethora of disease conditions. Sialic acids are carbohydrates, present on cell surfaces or soluble proteins. Sialic acid-binding immunoglobulin-like lectins (Siglecs) recognize and bind to sialic acids. These are widely expressed on various types of immune cells. Siglecs modulate immune activation and can promote or inhibit ROS generation under different contexts. Siglecs promote ROS-dependent cell death in neutrophils and eosinophils while limiting oxidative stress associated with chronic obstructive pulmonary disease (COPD), sickle cell disease (SCD), coronavirus disease-2019 (COVID-19), etc. This review distinguishes itself in summarizing the current understanding of the role of Siglecs in moderating ROS production and their distinct effect on different immune cells; that ultimately determine the cellular response and the disease outcome. This is an important field of investigation having scope for both expansion and medical importance.